ANALYSIS OF LABOR SUPPLY ON THE PADDY FARMING IN SLEMAN DISTRICT - Uti Aliffiani; Jangkung Handoyo Mulyo; Ken Suratiyah (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2013)
This research was conducted (1) to understand the labor supply on the paddy farming (2) to estimate the factors affecting labor supply of farm household on the paddy farming (3) to understand source of farm household income and the contribution of farm household income. The primary method for this research is descriptive analysis. The research located in Margokaton Village, Sayegan Subdistrict, Sleman District were determined simple random sampling, there were 30 farm household of paddy farmers. The data was analyzed by paired sample t-test and multiple linier regression analysis by Ordinary Least Sugar(OLS). The result showed that (1) labor supply on paddy farming was 103,44 HKO/year which consists of family labor was 85,81 HKO/year and non family labor was 17,63 HKO/year, (2) labor supply of farm household on the paddy farming was affected positively by field area and technical irrigation (3) sources of farm household income were from farm income and non farm income meanwhile the contribution of farm income and non farm income to farm household income were 45,64% and 54,36% of. The contribution of paddy farming is 19,60% to farm household income.